Bone loss and aggravated autoimmune arthritis in HLA-DRβ1-bearing humanized mice following oral challenge with Porphyromonas gingivalis. Issue 1 (December 2016) - Sandal, Indra; Karydis, Anastasios; Luo, Jiwen; Prislovsky, Amanda; Whittington, Karen; Rosloniec, Edward; Dong, Chen; Novack, Deborah; Mydel, Piotr; Zheng, Song; Radic, Marko; Brand, David
Abstract Background The linkage between periodontal disease and rheumatoid arthritis is well established. Commonalities among the two are that both are chronic inflammatory diseases characterized by bone loss, an association with the shared epitope susceptibility allele, and anti-citrullinated protein antibodies. Methods To explore immune mechanisms that may connect the two seemingly disparate disorders, we measured host immune responses including T-cell phenotype and anti-citrullinated protein antibody production in human leukocyte antigen (HLA)-DR1 humanized C57BL/6 mice following exposure to the Gram-negative anaerobic periodontal disease pathogenPorphyromonas gingivalis. We measured autoimmune arthritis disease expression in mice exposed toP. gingivalis, and also in arthritis-resistant mice by flow cytometry and multiplex cytokine-linked and enzyme-linked immunosorbent assays. We also measured femoral bone density by microcomputed tomography and systemic cytokine production. Results Exposure of the gingiva of DR1 mice toP. gingivalis results in a transient increase in the percentage of Th17 cells, both in peripheral blood and cervical lymph nodes, a burst of systemic cytokine activity, a loss in femoral bone density, and the generation of anti-citrullinated protein antibodies. Importantly, these antibodies are not produced in response toP. gingivalis treatment of wild-type C57BL/6 mice, andP. gingivalis exposure triggered expression of arthritis in arthritis-resistant mice. Conclusions Exposure of gingival tissues toP. gingivalis has systemic effects that can result in disease pathology in tissues that are spatially removed from the initial site of infection, providing evidence for systemic effects of this periodontal pathogen. The elicitation of anti-citrullinated protein antibodies in an HLA-DR1-restricted fashion by mice exposed toP. gingivalis provides support for the role of the shared epitope in both periodontal disease and rheumatoid arthritis. The ability ofP. gingivalis to induce disease expression in arthritis-resistant mice provides support for the idea that periodontal infection may be able to trigger autoimmunity if other disease-eliciting factors are already present.